Simultaneous Determination of C18 Fatty Acids in Milk by GC-MS - Meiqing Chen; Yangdong Zhang; Fengen Wang; Nan Zheng; Jiaqi Wang (Separations, 2021)
The determination of C18 fatty acids (FAs) is a key and difficult aspect in FA profiling, and a qualified method with good chromatographic separation and high sensitivity, as well as easy methylation, is required. A GC-MS method was established to simultaneously determine C18 FAs in milk. To simplify the methylation protocol for milk samples, besides a base-catalyzation methylation (50 °C for 20 min), the necessity of an additional acid-catalyzation was also studied using different temperatures (60 °C, 70 °C, 80 °C, and 90 °C) and durations (90 min and 150 min). The results showed that the chromatographic resolution was improved, although three co-eluted peaks existed. The base-catalyzation was sufficient, and an additional acid-catalyzation was not necessary. The proposed method was validated with good sensitivity, linearity, accuracy, and precision, and then applied in determining C18 FAs in 20 raw milk and 30 commercial milk samples. UHT milk presented a different profile of C18 FAs from raw milk and PAS milk samples, which indicated that excessive heating could change the profile. Overall, the proposed method is a high-throughput and competent approach for the determination of C18 FAs in milk, and which presents an improvement in chromatographic resolution and sensitivity, as well as a simplification of methylation.